An On-Chip Planar Inverted-F Antenna at 38 GHz for 5G Communication Applications - Syed Muhammad Ammar Ali (International Journal of Antennas and Propagation)
This paper presents an on-chip planar inverted-F antenna (PIFA) implemented in TSMC 180 nm CMOS process technology. The antenna operates at a 5 G millimeter-wave center frequency of 38 GHz. The ultrathick metal (UTM) layer of the technology is utilized to implement the on-chip antenna (OCA). The OCA is positioned close to the edge of the microchip for improving the gain performance of the antenna. The open end of the antenna is folded to develop a top-loaded PIFA structure yielding better 50 Ω impedance matching and wider bandwidth. On-wafer measurements are conducted through the Cascade Microtech Summit 11K probe-station and ZVA-50 vector network analyzer to measure the return loss and gain of the fabricated on-chip antenna. The measurements are performed after placing the fabricated OCA over a 3D-printed plastic slab to minimize the reflections from the metallic chuck of the probe station. The measurement results show that the fabricated on-chip PIFA achieves a minimum return loss of 14.8 dB and a gain of 0.7 dBi at the center frequency of 38 GHz. To the best of the authors’ knowledge, the presented OCA is the first on-chip PIFA designed, fabricated, and tested at the 5G millimeter-wave frequency of 38 GHz.